The predictive power of the yeld curve: the portuguese case - Martins, Filipe Afonso Borges De Castro De Oliveira (2020)
This work project studies the historical relation ship between the yield curve and real economic activity in Portugal, comparing results with Germany and Spain.Controlling for other indicators, on average,each percentage point increase in the Portuguese yield spread was associated with a 0.6 pp.increase in real growth over the subsequent year. In general,a longer maturity short-term rate is preferable in Portugal, similarly to Spain. To forecast recessions, as expected, the lower the slope of the yield curve,the higher the probability of a downturn. Spain, an expanded model is more effective for Portugal,whilst for Germany the univariate setup was already relatively a curate. These onclusions could be use ful in Risk Management or in the improvement of a Portuguese leading economic indicator.